A Possible Change in Mass Balance of Greenland and Antarctic Ice Sheets in the Coming Century - Ohmura, Atsumu; Wild, Martin; Bengtsson, Lennart (American Meteorological Society, 1996)
A high-resolution GCM is found to simulate precipitation and surface energy balance of high latitudes with high accuracy. This opens new possibilities to investigate the future mass balance of polar glaciers and its effect on sea level. The surface mass balance of the Greenland and the Antarctic ice sheets is simulated using the ECHAM3 GCM with TI06 horizontal resolution. With this model, two 5-year integrations for the present and doubled carbon dioxide conditions based on the boundary conditions provided by the ECHAM1/T21 transient experiment have been conducted. A comparison of the two experiments over Greenland and Antarctica shows to what extent the effect of climate change on the mass balance on the two largest glaciers of the world can differ. On Greenland one sees a slight decrease in accumulation and a substantial increase in melt, while on Antarctica a large increase in accumulation without melt is projected. Translating the mass balances into terms of sea-level equivalent. the Greenland discharge causes a sea level rise of 1.1 mm yr−1, while the accumulation on Antarctica tends to lower it by 0.9 mm yr−1. The change in the combined mass balance of the two continents is almost zero. The sea level change of the next century can be affected more effectively by the thermal expansion of seawater and the mass balance of smaller glaciers outside of Greenland and Antarctica.